Giant Cell Tumor of Tendon Sheath in the Knee - Malek Ghnaimat; Mohannad Alodat; Mohammad Aljazazi; Raad Al-Zaben; Jamal Alshwabkah (Electronic Physician, 2016)
The giant cell tumor of the tendon sheath (GCTTS) is a benign lesion which arises from the synovium of a joint, bursa or tendon sheath, with 85% of the tumors occurring in the fingers and 12% of the tumors located in large joints such as the knee and ankle. The GCTTS is usually monoarticular, slowly proliferative and rarely locally aggressive. This paper reports three cases of this rare lesion in the knee. Patients presented with painful swelling in the anterior knee, MRI showed localized soft tissue masses which were able to be excised. A follow up of the cases showed no recurrences. This case report emphasizes the importance of considering GCTTS in the differential diagnosis of soft tissue swelling and pain in large joints.